Pertumbuhan bayam merah (Alternanthera amoena voss) Secara Hidroponik Dengan Konsentrasi Nutrisi Dan Media Tanam Yang Berbeda - Utami, Ken, Dra. Aminah Asngad, S.Si., M.Si (2016)
Hydrophonic is a system of planting without use soils medium but use water for medium subtituter of soil. The purpose of this study was to determine the effect of nutrient concentrations and different growth medium on the growth of red spinach plants hydroponically. This study used a completely randomized design (CRD) with two factors: concentration of nutriens and growth medium with three replications. The analysis technique used descriptive quantitative use Two way Annova with significance level of 5%, followed by comparing the average of each treatment or Estimated Marginal Means. The results of the study of plant height F count <F table is 0.354 <2.928. The number of leaves of plants F count <F table is 1.944 <2.928. Broad leaves of plants F count <F table is 0.904 <2.928. Then it can be concluded growing plant nutrient concentrations and medium that give an effect not to be real. Plant height is the most optimal nutrient concentration 5 ml / liter with coconut fiber. The number of leaves and leaf area are the most optimal nutrient concentrations of 5 ml/liter and 4 ml / liter with rockwool.